Afterword: Amazing Grace. Issue 1 (1st March 2022) - Lloyd, Vincent
Abstract: On one hand, the excess marked by grace is unquantifiable, challenging the order of the world and opening to the new. On the other hand, grace and its promise are used by the powers that be to naturalise themselves and manage dissent. Black American discourse around racism illustrates this tension, with elected leaders like Barack Obama using grace in the service of power, social movement leaders suspicious of performances tied to grace, and scholars navigating our instinct to be critical and our instinct to use critique as its own form of grace. Meditating on these questions opens lines of inquiry where theology and anthropology connect, including around the aesthetics of grace, the morality of grace, the relationship between trauma and grace, and the authorship of grace.